2020
DOI: 10.1007/s42399-020-00534-3
|View full text |Cite
|
Sign up to set email alerts
|

The Model for End-Stage Liver Disease-Sodium Score at Admission Is Prognostic of Covid-19 Disease Severity

Abstract: Covid-19 is a systemic viral respiratory illness that can cause gastrointestinal manifestations. There is evidence that Covid-19 can infect liver tissue and may cause transaminemia. A prognostic model is needed to aid clinicians in determining disease severity. The Model for End-Stage Liver Disease-Sodium (MELD-Na) score is a mortality assessment tool in liver transplant patients that has been found to be prognostic in other clinical situations. This study aimed to determine if the MELD-Na score was associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Wagner et al. suggested that hypoalbuminemia and elevated transaminases in COVID-19 are predictors of disease severity, and proposed the MELD-na score to assess the severity of COVID-19 patients [ 24 , 25 ]. Zou et al.…”
Section: Discussionmentioning
confidence: 99%
“…Wagner et al. suggested that hypoalbuminemia and elevated transaminases in COVID-19 are predictors of disease severity, and proposed the MELD-na score to assess the severity of COVID-19 patients [ 24 , 25 ]. Zou et al.…”
Section: Discussionmentioning
confidence: 99%
“…[ 33 ] We are aware of only one study on MELD-Na score and its association with increased mortality in COVID-19 which was performed on 107 hospitalized COVID-19 patients and did not adjust for confounding variables or specifically investigate critically ill COVID-19 patients with liver injury. [ 8 ] Our study included a larger sample size and focused on critically ill COVID-19 patients with acute liver injury. The mean MELD-Na score for our sample was approximately 14 points which represents the lowest mortality range.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] The Model for End-Stage Liver Disease modified for Sodium concentration (MELD-Na) score is a prognostic tool for patients awaiting liver transplant that is also commonly applied to estimate mortality in acute liver failure patients. [ 7 ] A study among general COVID-19 patients found that the MELD-Na score predicted mortality from renal failure;[ 8 ] however, literature on MELD-Na predicting mortality for liver injury in COVID-19 patients is lacking.…”
Section: Introductionmentioning
confidence: 99%